Synthesis and characterization of novel 1,8-Naphthalimide derivatives containing 1,3-oxazoles, 1,3-thiazoles, 1,2,4-triazoles as antimicrobial agents - Al-Majidi, Suaad M H; Ahmad, Mohammed R; Khan, Ayad Kareem (Al-Nahrain Journal of Science, 2018)
This research include developing new heterocyclic derivatives of 1,8-naphthalimides bearing 1,3-oxazole, 1,3-thiazole and 1,3,4-triazole moieties as the following: Direct imidation of 1,8-naphthalic anhydride with ethylglycinate in dimethylsulfoxide as solvent under reflux at high temperature for sixteen hours to obtain the N-ester-1,8-naphthalimide(1). Then conversion of this ester into (urea, thiourea, semicarbazide, phenylsemicarbazide, thiosemicarbazide and phenylthiosemicarbazide) derivatives through its reaction with (urea, thiourea, semicarbazide, phenylsemicarbazide, thiosemicarbazide and phenylthiosemicarbazide) respectively to give compounds (2,6,10,12,14 and16). Then cyclization of these compounds by using different reagents. The first cyclization of compounds (2 and 6) by using p-substituted phenacylbromide to give oxazole derivatives (3-5) and thiazole derivatives (7-9) respectively. Furthermore triazole derivatives were prepared through the second cyclization of compounds (10,12,14 and16) in alkaline media(4N. NaOH) to give compounds (11,13,15 and 17) respectively.The structure of the newly synthesized compounds was identified by their FTIR, and some of them by 1H-NMR, 13C-NMR spectral data and some physical properties and some specific reactions.Also new compounds were screened in three concentration for their in vitro antimicrobial activity against both Gram (+ve) such as Staphylococcus aureus, Bacillus and Gram (-ve) Escherichia Coli, pseudomonas aeuroginosa bacteria and against Candida albicans fungal and they were found to exhibit good to moderate antimicrobial activities.